Global Business Cycles: Degree of Synchronization in the Current Downturn Is Unprecedented - Vladimir Kuzin; Martin Hillebrand (Weekly Report, 2009)
Empirical data analysis shows that the business cycles of industrialized nations demonstrate a fairly strong degree of synchronization in periods of growth, and a lesser degree of synchronization during periods of contraction. The current recession, however, breaks this pattern: the business cycles of industrialized nations have exhibited an unprecedented degree of synchronization since the start of the crisis. In the worst economic downturn since the end of the Second World War, the most important national economies have been drawn one after another into the maelstrom of global recession. In this paper we present a method for measuring business-cycle synchronization between individual countries. In our comparison of the current crisis with previous recessions, a focus is placed on the G7 nations and Germany's most important trading partners.
Keywords: E32; C22; 330; Business cycle synchronisation; Markov switching models